Shadows of war : violence, power, and international profiteering in the twenty-first century - Nordstrom, Carolyn, 1953- (California series in public anthropology, 2004)
In this provocative and compelling examination of the deep politics of war, Carolyn Nordstrom takes us from the immediacy of war-zone survival, through the offices of power brokers, to vast extra-legal networks that fuel war and international profiteering.